Prosody control for speaking and singing styles - Shih, C; Kochanski, G (International Speech Communication Association (ISCA), 2001)
By proper control of prosody, text-to-speech systems already have the capacity to imitate distinctive speaking styles. We show two examples where we can capture the critical features: the singing style of Dinah Shore and the speaking style of Martin Luther King Jr. The styles are described by Stem-ML tags (soft template mark-up language), which offers the flexibility needed to control accent shapes, phrasal pitch contours, and amplitude profiles, for speech as well as for singing.